Visualização de Dados Governamentais Abertos: aportes para análise de plataformas - Souza, Tainá Regly de Moura (2021)
It deals with the use of visualizations as a tool to democratize the reach of public information by platforms that deal with Open Government Data. It aims to investigate how the data visualization resource is being applied by these government portals to facilitate the access of Brazilian citizens. It achieves this goal by applying systematized parameters based on literature related to the disciplines of Data Visualization, Information Architecture and Usability to conduct an analysis of the Vision, Transparency Portal and SIGA Brasil platforms. It points out that there is great fragmentation of the platforms that work with Open Government Data and registers the need for centralization and unification of data to broaden the community's access. It concludes by identifying strong and weak points, as well as problems related to data visualization, information architecture and usability that influence the access and interpretation of the data published in the three indicated platforms. It suggests improvements based on the adversities detected aiming at the improvement of the Brazilian platforms that have data visualization resources.